A kinetic and thermochemical database for organic sulfur and oxygen compounds1. Issue 20 (28th May 2015) - Class, Caleb A.; Aguilera-Iparraguirre, Jorge; Green, William H.
<x xml:space="preserve">Abstract</x> Potential energy surfaces and reaction kinetics were calculated for reactions involving sulfur and oxygen, which are potentially relevant in combustion and desulfurization chemistry.